2013
DOI: 10.1093/cercor/bht285
|View full text |Cite
|
Sign up to set email alerts
|

Neural Coupling of Cooperative Hand Movements: A Reflex and fMRI Study

Abstract: The neural control of "cooperative" hand movements reflecting "opening a bottle" was explored in human subjects by electromyographic (EMG) and functional magnetic resonance imaging (fMRI) recordings. EMG responses to unilateral nonnoxious ulnar nerve stimulation were analyzed in the forearm muscles of both sides during dynamic movements against a torque applied by the right hand to a device which was compensated for by the left hand. For control, stimuli were applied while task was performed in a static/isomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 67 publications
7
85
0
1
Order By: Relevance
“…Percutaneous activation of peripheral axons with electrical stimulation, such as NMES, sends a volley of afferent feedback into the spinal cord (4) that can evoke responses in the contralateral limb (8,24,29). For example, electrical stimulation (five 1-ms pulses at 300 Hz) of the superficial radial nerve at the level of the hand (cutaneous afferents) evokes an interlimb reflex depression of EMG activity at a medium (75-120 ms) latency in contralateral flexor carpi radialis during an ongoing contraction (50% MVC) (32).…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous activation of peripheral axons with electrical stimulation, such as NMES, sends a volley of afferent feedback into the spinal cord (4) that can evoke responses in the contralateral limb (8,24,29). For example, electrical stimulation (five 1-ms pulses at 300 Hz) of the superficial radial nerve at the level of the hand (cutaneous afferents) evokes an interlimb reflex depression of EMG activity at a medium (75-120 ms) latency in contralateral flexor carpi radialis during an ongoing contraction (50% MVC) (32).…”
Section: Discussionmentioning
confidence: 99%
“…-Neuroplasticity is supposed to be the neuronal substrate for the effects of functional training -The newly discovered mechanism of neural coupling as manifested in cooperative hand movements 41 should be modelled in animals to investigate the underlying neuronal circuitries.…”
Section: Clinical Problems Requiring Basic Animal Researchmentioning
confidence: 99%
“…41 Consequently, after a cervical SCI or a stroke both hemispheres become involved in the control of the paretic hands during such cooperative movements. 47 For the rehabilitation of upper limb movements this has the consequence that a training of cooperative hand movements required during a number of daily life activities, eventually in combination with an exclusive training of the affected arm/hand (Constraint Induced Movement Therapy) can improve outcome of hand function in subjects suffering a CNS damage.…”
mentioning
confidence: 99%
“…For example, cooperative hand movements are required when opening a bottle, that is, the action of the two hands is different, but they support each other. Previous research on cooperative hand movements indicated that neural coupling between the two hands provides a fast and accurate automatic coordination of bilateral hand movements in ADL (Dietz et al, 2015). This neural coupling is reflected in the appearance of bilateral reflex EMG responses to unilateral arm nerve stimulation.…”
Section: Introductionmentioning
confidence: 99%